2009
DOI: 10.1093/eurjhf/hfn026
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol‐induced heart failure in the rat is associated with nitric oxide‐dependent functional alterations of cardiac function

Abstract: AimsThe role of nitric oxide (NO) in heart failure (HF) is complex and remains controversial. We tested the hypothesis that the role of NO in isolated atria and cardiomyocytes is altered in isoproterenol-induced HF. Methods and resultsRats received isoproterenol (ISO, 5 mg/kg/day, intraperitoneally) or vehicle for 1 week. Haemodynamic parameters were obtained by left ventricular catheterization. Effects of NOS inhibition on isolated atria and on electrically paced left ventricular myocytes were determined. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
77
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 33 publications
(37 reference statements)
14
77
0
4
Order By: Relevance
“…In contrast, iNOS is a cytokine-inducible isoenzyme. In healthy heart, physiological amounts of NO may help to sustain cardiac inotropy [Krenek et al, 2009]. It is our hypothesis that in the ISO-induced MI model, the hypotensive effect observed after ISO administration, in the preinfarct stage [Chagoya de Sánchez, 1997], is mediated by NO and might be critical for the MI development.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, iNOS is a cytokine-inducible isoenzyme. In healthy heart, physiological amounts of NO may help to sustain cardiac inotropy [Krenek et al, 2009]. It is our hypothesis that in the ISO-induced MI model, the hypotensive effect observed after ISO administration, in the preinfarct stage [Chagoya de Sánchez, 1997], is mediated by NO and might be critical for the MI development.…”
Section: Introductionmentioning
confidence: 89%
“…Coronary heart disease accounts for more than 40% of cardiovascular deaths and its most serious form, acute myocardial infarction (AMI), is the principal cause of chronic heart failure 1 . Elevated catecholamines are known risk factors for a cardiovascular event and the synthetic catecholamine, isoprenaline has been used for about a half a century for inducing AMI and subsequent heart failure in small laboratory animals [7][8][9][10] . In our previous study, we found in a very small number of animals some correlations among various parameters in healthy and AMIinduced animals 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adrenergic agonists such as isoproterenol can induce cardiac hypertrophy in experimental animals [6][7][8]. Isoproterenol-induced cardiac hypertrophy is a reliable, reproducible, and well-characterized model of pathological cardiac hypertrophy [9,10].…”
Section: Introductionmentioning
confidence: 99%